Etnomatematika Terhadap Konsep Geometri Pada Ukiran Toraja - Novita Kala Pangadongan; Ariantje Dimpudus (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
The conscious or unconscious entry of mathematics into various aspects of life is certainly interesting to study such as from a cultural point of view. What can bridge the gap between culture and mathematics is ethnomathematics. Ethnomathematics is a study of the relationship between mathematics and culture. The study of mathematics in culture needs to be developed further to be able to provide an overview to the public about the role of mathematics in culture. one of the tribes that is rich in culture is Toraja, for example in Toraja carving which is a cultural heritage that is passed down from generation to generation until now there is the concept of geometry. Therefore, the purpose of this research is how the concept of geometry in Toraja carving using qualitative research methods ethnographic approach.